Features, Challenges and Opportunities of Population Ageing: Sri Lanka Perspective - Dissanayake, Lakshman (UNFPA, 2016)
According to the standard projection, the elderly population will increase in the future at an exponential rate (Dissanayake, 2016). In 2012, the number of older persons was 2,520,573 and it is expected to increase to 5,118,094 in 2037, which is a 103 percent increase within a 25 year time period. The population ageing taking place in Sri Lanka is a common feature of many developed and developing countries in the world today. This phenomenon is occurring mainly due to the decline in fertility and mortality and the resultant increase in life expectancy, which is accompanied by the socio-economic developments of the country – See more at: http://srilanka.unfpa.org/publications/features-challenges-and-opportunities-population-ageing-sri-lankan-perspective#sthash.PqdgHcKB.dpuf
Keywords: Features, Challenges and Opportunities of Population Ageing: Sri Lanka Perspective